Design and construction of a multi-sensor position monitoring system applied to key components of synchrotron sources - Wang, Wei; Tang, Zheng; He, Xiao-Ye; Zhang, Qiang (Nuclear science and techniques, 2016)
High-accuracy position monitoring of key components is required for modem synchrotron sources, such as free-electron lasers and diffraction-limited storage rings. Although various position monitoring sensors have been adopted to monitor the displacement of key compo- nents in each direction in real time, these monitoring sys- tems are usually based on their own coordinate system. Data from such systems are meaningful when evaluating and examining the data from each positioning monitoring system in a unified coordinate system. This paper presents the design and construction of a multi-sensor position monitoring system （MPMS）. A hydrostatic levelling system, a wire position sensor （WPS） and a tiltmeter are fixed to a stainless steel plate that has been calibrated by a coordinate-measurement machine. Several plates form the MPMS. The system must compensate for the sag of the stretched wires so that the WPSs create a straight line. The method of the coordinate transformation from the sensor coordinate system to the MPMS coordinate system was thoroughly studied. An experimental MPMS that includes five plates was setup in a 20-m tunnel, and a validation study to verify fully the feasibility of the MPMS was performed.